The use of literary texts in the English-as-a-foreign-language classroom: towards an aesthetic approach - Fernández Fernández, Raquel (Pulso. Revista de educación, 2006)
The present article aims at exploring the use of literary texts in the English as a Foreign Language classroom. The author uses the concepts of efferent reading and aesthetic reading developed by L. M. Rosenblatt, and demonstrates how and why the efferent reading is preferred in the Spanish educational system today. Later on, the author gives reasons to explain this tendency and support a more aesthetic approach to the reading of literary texts in the EFL classroom. To do that, the importance of training teachers to use literature properly is highlighted, and several pedagogical guidelines to improve teacher training and to achieve a more adequate and balanced use of the literary text are presented.